Features and functions of covalently linked proteins in fungal cell walls - De Groot, P.W.J.; Ram, A.F.; Klis, F.M.
The cell walls of many ascomycetous yeasts consist of an internal network of stress-bearing polysaccharides, which serve as a scaVold for a dense external layer of glycoproteins. GPI-modiWed proteins are the most abundant cell wall proteins and often display a common organization. Their C-terminus can link them covalently to the polysaccharide network, they possess an internal serineand threonine-rich spacer domain, and the N-terminal region contains a functional domain. Other proteins bind to the polysaccharide network through a mild-alkali-sensitive linkage. Many cell wall proteins are carbohydrate/glycan-modifying enzymes; adhesion proteins are prominent; proteins involved in iron uptake are present, and also specialized proteins that probably help the fungus to survive in its natural environment. The protein composition of the cell wall depends on environmental conditions and developmental stage. We present evidence that the cell wall of mycelial species of the Ascomycotina is similarly organized and contains glycoproteins with comparable functions.
Keywords: GPI-PROTEINS; PIR-PROTEINS; PROTEOMICS; CELL WALL POROSITY; IRON UPTAKE; ANTIGENICITY; HYDROPHOBICITY; BIOWLMS; HOST-PATHOGEN INTERACTIONS